KAJIAN HUBUNGAN SATUAN FUNGSI DALAM PENEGAKAN HUKUM DI POLRES BOYOLALI - PRIYANTO, FX. (Dinamika Hukum, 2017)
The purpose of this study is to determine the extent to which the relationshipbetween functions in law enforcement in the District Police Boyolali in accordancewith Perkap No. 23 of 2010, September 30, 2010.The background of this research is that in the context of the execution ofduties as law enforcers, members of the Police who are in the field or in the officialstill lack understanding of translations of meaning and meaning of protector,protector and public servant.The research method begins by conducting initial research in the form ofdata collection that support the problem under study. Furthermore, the researchconducted in Polres Boyolali, while the data collection techniques in the form ofinterviews, documentation studies. All the data collected is analyzed qualitatively, ie,the description based on the reality associated with the theories.The results showed that, the relationship between the functions in lawenforcement in Polres Boyolali has been running well, Police Smile Program /Commend Center recently launched by the Chief of Police on January 28, 2017 inPolda Central Java also went well. With this program, it is hoped that the relationshipbetween the community and the Police will be closer because the people reporting theproblem or making a complaint to download Police Smile / E-Complain program sothey do not have to come to the Polres office.Keywords: Relationship among functions in law enforcement.